The enhancement of pyridine degradation by Rhodococcus KDPy1 in coking wastewater. Issue 1 (15th November 2018) - Zhang, Yuxiu; Zhang, Yiming; Xiong, Jie; Zhao, Zhehui; Chai, Tuanyao
Abstract: Pyridine is a typical nitrogen heterocyclic and recalcitrant organic compound in coking wastewater. The pyridine-degrading bacterial strain KDPy1 was isolated from aerobic sludge in a coking wastewater treatment plant. The homology analysis based on 16S rDNA sequences suggested that KDPy1 belongs to Rhodococcus sp. The optimum temperature and pH for pyridine degradation by KDPy1 were 37°C and 7–8, respectively. The strain KDPy1 degraded 1442 mg/L of pyridine nearly 99.6% after 48 h, and the high concentration of 1442 mg/L pyridine did not show an inhibitory effect on its degradation. The degradation kinetics of pyridine were fitted with the Monod model. Furthermore, KDPy1 was capable of degrading pyridine efficiently in the synthetic wastewater containing quinoline and phenol. KDPy1 could degrade pyridine and reduce the total organic carbon in the real coking wastewater. These results showed that KDPy1 had a potential for improving the removal of pyridine from coking wastewater. Abstract : This work demonstrated the practical application of pyridine-degrading bacterium KDPy1 by evaluating the removal of pyridine, quinoline and TOC in actual coking wastewater.